Germany's war debt to Greece : a burden unsettled - Christodoulakis, Nicos; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
The book chronicles the Occupation Loan that was forcibly obtained by the Third Reich from the Greece in 1942-1944 and demonstrates why Greece's claim for the repayment of the loan is still valid. To overcome the absence of a normal debt agreement between the two countries, various assessments of its current value are presented and discussed.
Keywords: World War, 1939-1945 -- Reparations -- Germany; World War, 1939-1945 -- Reparations -- Greece; Greece -- History -- Occupation, 1941-1944.; Germany -- Foreign relations -- Greece; Greece -- Foreign relations -- Germany